Commercial trade of wild animals: examining the use of the IUCN Red List and CITES Appendices as the basis for corporate trade policies - Green, Jennah; Schmidt-Burbach, Jan; Elwin, Angie (Frontiers in Conservation Science, 2022)
Wildlife exploitation is considered a predominant factor driving global biodiversity loss and zoonotic disease transmission, in addition to a range of concerns for animal welfare and ecosystem health. One of the ways in which wild animals are exploited is for commercial trade as exotic pets, fashion products, luxury foods, traditional medicine, entertainment, ornaments and more. While the trade in some wildlife species is restricted or prohibited under various domestic and international laws, many species are not bound by legal protection and are traded in largely unmonitored numbers with the potential for severe consequences. Companies, particularly large e-commerce platforms, are increasingly adopting policies to restrict the legal trade in wild animals. Due to the absence of clear guidelines for corporate services of wildlife trade, these policies commonly adopt pre-determined species lists, such as the International Union for the Conservation of Nature’s (IUCN) Red List of Threatened Species or the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) Appendices, as the basis for ‘negative lists’ to guide which species to restrict trade in. However, these databases were not intended for this application and there has been no assessment of their use for this purpose. Here, we summarise and compare the scale and scope of species listed on the IUCN Red List and the CITES Appendices, to discuss how much additional protection these lists provide wild animals if used as policy instruments to guide corporate wildlife trade restrictions beyond the relevant legal bounds. Our results demonstrate that using one list or another would likely omit taxa of conservation concern from protection, and using both lists in conjunction would still not comprehensively reflect all species vulnerable to extinction as a result of exploitation. Further, neither list can mitigate the animal welfare and public health concerns inherently associated with all commercial wildlife trade. We recommend that companies looking to develop policies relating to commercial wildlife trade consider going beyond the scope of predetermined species lists to help mitigate the harmful effects of commercial wildlife exploitation via trade for all wild animals.